1. The value of trace minerals in a wintering and fattening ration. 2. Self-feeding grain in drylot vs. self-feeding on bluestem pasture. - Smith, E.F.; Cox, R.F.; Baker, F.H. (Kansas Agricultural Experiment Station, 2012)
Thirty head of good quality Hereford steer calves, 10 head to a lot, were used in the study. They were the lightest calves of a shipment of 220 steer calves from the Brite Ranch at Marfa, Texas. They cost 29 cents a pound delivered to Manhattan, Kan., November 3, 1952. They were fed prairie hay and 1 pound of soybean pellets until they were started on test December 19, 1952. All weights are full weights taken about 7: 00 a.m. before feeding, except the initial and final weights of the full-feeding period, which were taken after an overnight stand in drylot. The trace minerals were fed as a trace mineral premix added to the soybean oilmeal to furnish the following amounts in milligrams per head daily in the wintering and fattening ration, respectively: manganese 25.0, 56.3; iodine .87, 1.97; cobalt .55, 1.25; iron 20.5, 46.13; copper 1.62, 3.65; and zinc 1.52, 3.42.
Keywords: Beef; Trace mineral; Performance; Gain